Dynamic nuclear polarization studies on deuterated nitroxyl spin probes. (23rd May 2017) - David Jebaraj, D.; Utsumi, Hideo; Milton Franklin Benial, A.
Abstract : Detailed dynamic nuclear polarization and electron spin resonance studies were carried out for 3‐carbamoyl‐2, 2, 5, 5‐tetramethyl‐pyrrolidine‐1‐oxyl, 3‐carboxy‐2, 2, 5, 5‐tetramethyl‐pyrrolidine‐1‐oxyl, 3‐methoxycarbonyl‐2, 2, 5, 5‐tetramethy pyrolidine‐1‐oxyl nitroxyl radicals and their corresponding deuterated nitroxyl radicals, used in Overhauser‐enhanced magnetic resonance imaging for the first time. The dynamic nuclear polarization parameters such as dynamic nuclear polarization (DNP) factor, longitudinal relaxivity, saturation parameter, leakage factor and coupling factor were estimated for deuterated nitroxyl radicals. DNP enhancement increases with agent concentration up to 3 mm and decreases above 3 mm . The proton spin–lattice relaxation time and the longitudinal relaxivity parameters were estimated. The leakage factor increases with increasing agent concentration up to 3 mm and reaches plateau in the region 3–5 mm . The coupling parameter shows the interaction between the electron and nuclear spins to be mainly dipolar in origin. DNP spectrum exhibits that the full width at half maximum values are higher for undeuterated nitroxyl radicals compared with deuterated nitroxyl radicals, which leads to the increase in DNP enhancement. The ESR parameters such as, the line width, line shape, signal intensity ratio, rotational correlation time, hyperfine coupling constant and g‐factor were calculated. The narrow line width was observed for deuterated nitroxyl radicals compared with undeuterated nitroxyl radicals, which leads to the higher saturation parameter value and DNP enhancement. The novelty of the work permits clear understanding of the DNP parameters determining the higher DNP enhancement compared with the undeuterated nitroxyl radicals. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : Dynamic Nuclear Polarization (DNP) properties and ESR studies were carried out for few deuterated nitroxyl radicals. The narrow line width was observed for deuterated nitroxyl radicals compared with undeuterated nitroxyl radicals The coupling parameters show the interaction between the electron and nuclear spin is mainly dipolar in origin. The novelty of the work permits clear understanding of the DNP parameters determining the higher DNP enhancement for deuterated nitroxyl radicals.